2012
DOI: 10.1007/s11746-012-2180-1
|View full text |Cite
|
Sign up to set email alerts
|

Simplex‐Centroid Mixture Design Applied to the Aqueous Enzymatic Extraction of Fatty Acid‐Balanced Oil from Mixed Seeds

Abstract: A one‐step method was developed to extract oil from a mixture of soybeans, peanuts, linseeds, and tea seeds using an aqueous enzymatic method. The proportion of the four seeds was targeted in accordance with a fatty acid ratio of 0.27 (SFA, saturated fatty acid(s)): 1 (MUFA, monounsaturated fatty acid(s)): 1 (PUFA, polyunsaturated fatty acid(s)), and the oil extraction yield was maximized by applying the simplex‐centroid mixture design method. Three models were developed for describing the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…These restrictions affect profit margins and/or increase soybean oil and meal costs (Anonymous, 2002). Enzyme-assisted aqueous extraction processing (EAEP) has recently received interest as an environmentally-friendly alternative to conventional oil-extraction technologies (Lamsal and Johnson, 2007;Campbell and Glatz, 2009;de Moura et al, 2009;Jung et al, 2009;Li et al, 2013). EAEP can achieve $97% oil recovery from soybeans, by using enzymes to free the oil from solid matrix.…”
Section: Introductionmentioning
confidence: 99%
“…These restrictions affect profit margins and/or increase soybean oil and meal costs (Anonymous, 2002). Enzyme-assisted aqueous extraction processing (EAEP) has recently received interest as an environmentally-friendly alternative to conventional oil-extraction technologies (Lamsal and Johnson, 2007;Campbell and Glatz, 2009;de Moura et al, 2009;Jung et al, 2009;Li et al, 2013). EAEP can achieve $97% oil recovery from soybeans, by using enzymes to free the oil from solid matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The fatty acid composition was carried out by an Agilent 6890-5973 gas chromatography-mass spectrometer (GC-MS; Agilent Technologies, CA, USA) analysis according to Li et al (2013).…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…So far, most studies on CSO have been focused on chemical characterization (Su et al, 2014;Wang X.Q. et al, 2014), especially some active components and antioxidant capacity, the extraction (Li et al, 2013;Lim et al, 2013), refining process (Na, 2008), and adulteration (Hai and Wang, 2006). Few studies have been reported on its formation of degradation compounds during heating.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical extraction can result in low oil recovery and denatured proteins, and the use of organic solvents may cause solvent residue and non-friendly to environment. The AEE for oil extraction as an emerging technology, enables simultaneous recovery of oil and protein from most oil materials (Li et al, 2013a). Enzymes are useful for the extraction of oil due to their high efficiency and specificity.…”
Section: Introductionmentioning
confidence: 99%